Labour Market Frictions, Monetary Policy, and Durable Goods - Federico Di Pace; Matthias S. Hertweck (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
The standard two-sector monetary business cycle model suffers from an important deficiency. Since durable good prices are more flexible than non-durable good prices, optimising households build up the stock of durable goods at low cost after a monetary contraction. Consequently, sectoral outputs move in opposite directions. This paper finds that labour market frictions help to understand the so-called sectoral "comovement puzzle". Our benchmark model with staggered Right-to-Manage wage bargaining closely matches the empirical elasticities of output, employment and hours per worker across sectors. The model with Nash bargaining, in contrast, predicts that firms adjust employment exclusively along the extensive margin.
Keywords: E21; E23; E31; E52; 330; durable production; labour market frictions; sectoral comovement; monetary policy